2016
DOI: 10.1080/01448765.2016.1185645
|View full text |Cite
|
Sign up to set email alerts
|

The effect of sewage sludge biochar on peat-based growing media

Abstract: School of engineering, rMit university, Melbourne, australia; d Departamento de contaminación ambiental, instituto de ciencias agrarias, cSic, Madrid, Spain ABSTRACT Peat is the main component of growing media in horticulture. Increasing demand, environmental concerns and rising costs for peat make the search for alternative materials imperative. Much research has been performed aiming to find high quality and low cost substrates from different organic wastes such as compost and thus decrease peat consumption.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(42 citation statements)
references
References 39 publications
3
34
0
Order By: Relevance
“…The values of the hydrophysical properties are similar to those obtained by Méndez et al () for growing media prepared with peat and deinking sewage sludge biochar (pyrolysis temperature: 300 °C), using the same proportions than in the present study. Bulk density and air space were higher than the values obtained by Méndez et al () after mixing peat with sewage sludge biochar prepared at 450 °C.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…The values of the hydrophysical properties are similar to those obtained by Méndez et al () for growing media prepared with peat and deinking sewage sludge biochar (pyrolysis temperature: 300 °C), using the same proportions than in the present study. Bulk density and air space were higher than the values obtained by Méndez et al () after mixing peat with sewage sludge biochar prepared at 450 °C.…”
Section: Resultssupporting
confidence: 89%
“…In order to study the effect of hydrochar addition on peat properties, two hydrochar–peat mixtures were prepared by adding hydrochars (HSL or HUW) to peat (PT) at a 50% volume rate (PT + HSL and PT + HUW). This mixing ratio has been used in previous experiments where biochar has been used as a peat substitute (Méndez et al, , ). Samples were manually mixed with the help of a stainless steel spatula.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Kern et al [25], char materials must not necessarily remain on the level of a minor ingredient, but have the potential to be used as major constituents. Furthermore, since they are characterized by a high porosity and a high water-holding capacity, these materials may also be usable as a substitute for constituents, which are already established in the growing media market, but which have a limited supply [25,147,148]. For instance, rice hull-derived biochar would be a practically applicable amendment to improve the properties of growing media, in terms of an increased cation exchange capacity and water content [149].…”
Section: Greenhouse Ornamental Productionmentioning
confidence: 99%
“…Other research showed that a small amendment of biochar (1 to 5% by weight) to coconut (Cocos nucifera) fiber-tuff potting root substrate improved tomato (Lycopersicum esculentum) and pepper (Capsicum annuum) growth [23]. Biochar made from sewage sludge with commercial peat-based substrate was reported to increase macronutrient content of media, increase lettuce (Lactuca sativa) biomass by 184 to 270%, increase microbial biomass by 966%, and reduce the transfer of metal concentration compared to the direct use of sewage sludge [24].…”
Section: Introductionmentioning
confidence: 99%